"Death by PEEL?" The teaching of writing in the secondary English classroom in England. (2nd January 2019) - Gibbons, Simon
ABSTRACT: The teaching of writing is at the core of the secondary English teacher's work. There have long been contrasting ideas about the most effective approaches to supporting students as writers, and in recent years in England the evidence—from Ofsted, for example—would suggest that it is common for teachers to offer structures to scaffold students' writing in response to text, in particular. Whilst they may be helpful in some ways, there is a risk that these structures—often known by acronyms such as PEE (point, evidence, evaluation)—can be overused with a consequential marginalisation of student choice, voice and personal response. After a brief overview of the development of different approaches to teaching writing in English, this article—through consideration of a questionnaire and focus group interview—explores the teaching writing as it is experienced by one group of new entrants to the profession.